The first case of thrombocytopenia, anasarca, fever, renal impairment or reticulin fibrosis, and organomegaly (TAFRO) syndrome with unilateral adrenal necrosis: a case report - Yu Fujiwara; Kanae Ito; Akito Takamura; Kaoru Nagata (Journal of Medical Case Reports, 2018)
Abstract Background TAFRO syndrome, which was first reported in 2010 in Japan, is a relatively rare disease characterized by thrombocytopenia, anasarca, fever, renal impairment, reticulin fibrosis, and organomegaly. Although this disease is considered similar to multicentric Castleman disease, some of the clinical features, such as thrombocytopenia, are different from typical cases of multicentric Castleman disease. In addition, the etiology of TAFRO syndrome remains unknown and controversial. There have only been a few cases of TAFRO syndrome complicated with adrenal gland lesions, and all of them have had hemorrhagic involvement. Case presentation This report describes the case of a 46-year-old Asian man who presented with fever, epigastric pain, and back pain for 1 month. A computed tomographic scan revealed ascites, mild lymphadenopathy, and left adrenal necrosis without hemorrhage. A blood test showed thrombocytopenia, anemia, and elevated C-reactive protein, alkaline phosphatase, and creatinine levels. Based on the edema, severe thrombocytopenia, fever, reticulin myelofibrosis shown by bone marrow biopsy, mild lymphadenopathy, and progressive renal insufficiency, we diagnosed this patient as having TAFRO syndrome. He was successfully treated by immediate administration of glucocorticoids and tocilizumab. Conclusions There have been no previous reports of a case of TAFRO syndrome complicated with adrenal necrosis. Because the biopsy of the left adrenal gland revealed necrosis without any evidence of hemorrhage, we concluded that the unilateral adrenal necrosis in this case was caused by either ischemia from infarction or organomegaly itself under severe hypercytokinemia. This unusual clinical course is useful for further analysis of the etiology of TAFRO syndrome.